Variable factors controlling amorphous-zeolite phase transformation in metakaolin based geopolymer - Kannikar Juengsuwattananon (2018)
© 2017, Technical University of Kosice. All rights reserved. Metakaolin based geopolymer binder was synthesized using variable factors such as Na 2 O/SiO 2 , Na 2 O/Al 2 O 3 and H 2 O/Na 2 O molar ratios as well as curing time. Metakaolin was used as an alumino-silicate source incorporating with strong alkali activators; sodium hydroxide solution to undergo polycondenation and hence a formation of hardened geopolymeric binder. This work was aimed to investigate the effect of Na 2 O/SiO 2 , Na 2 O/Al 2 O 3 and H 2 O/Na 2 O ratios, as well as curing time on phase transformation. The chemical composition, phase development and microstructure of reaction products were examined by X-ray fluorescence, X-ray diffraction analysis and scanning electron microscopy with respect to their final compressive strength. Increasing the molar ratios of Na 2 O/Al 2 O 3 and H 2 O/Na 2 O tended to favour the transformation of amorphous gel to various types of crystalline zeolite. Sodalite (pseudo-phase zeolite) and zeolite belonging to the Faujasite group, as well as zeolite X and A were identified in these mixtures. Based on this study, systems that favoured the formation of zeolitic products tended to possess lower strengths.